Application of It Tools Among the Sports Staff of the University Athletics Club of Debrecen - Karikás, Krisztián; Ráthonyi, Gergely (Acta Carolus Robertus, 2024)
In modern sport, IT tools, the data they generate and data analysis are playing an increasingly important role. This is an area that opens up new opportunities for athletes and professionals alike, and I believe it is important to explore this. The purpose of this study was to present the technological tools used by professionals working in different sports teams and to present their views on the importance of these tools in their respective sports. My online questionnaire survey (Google Forms) included 22 questions, which in addition to 4 demographic questions, included 18 questions about IT tools in sport and their use and importance. 70% of the professionals surveyed consider IT tools in their sport to be useful, and 36% of respondents consider them to contribute greatly to the performance of their team. The professionals surveyed consider the IT tools and the data they generate in their sport to be important, but in many cases they are not exploiting their potential, which could even give them a competitive advantage over other teams.
Keywords: football; match analysis; IT tools